Characteristics of Patients With Trigeminal Neuralgia Referred to the Indonesian National Brain Center Neurosurgery Clinic - Prasetya, Mustaqim; Adidharma, Peter; Sulistyanto, Adi; Inoue, Takuro; Arham, Abrar (Frontiers in Surgery, 2022)
Trigeminal neuralgia (TN) is a debilitating neuropathic pain involving the fifth cranial nerve. There has been no study investigating the clinical and socio-economical characteristics of TN patients in Indonesia. A hundred patients were included in this study. Symptoms indicating a later stage of the illness, namely involvement of all trigeminal nerve branches, numbness, and concomitant persistent pain, were the common presentations found in our cohort. Only one TN diagnosis was made by a general practitioner (GP). None were immediately referred to a neurosurgeon following their diagnosis. Access to our clinic took as long as 4.7± 5.1 years (mean±SD) from the onset. Older age was a significant predictor of an increased likelihood of not knowing their illness upon the referral (21.9%, p=0.008). Upon their first presentation, 25.5% of the patients had experienced drug-related side effects due to prolonged medication. Only 50% of the patients were compensated by the universal health coverage (UHC) system. Seven patients spent ≥50 million rupiahs, and eight patients had already lost their jobs. In conclusion, early contact with a neurosurgeon contributes to better management of TN, both for the patients and Indonesia’s health care system. A refined understanding of TN nature is still needed in this country.